Desempenho de Melia azedarach L. sob diferentes tipos de tratamentos de partículas, proporções de cimento e aditivos, na fabricação de painéis cimento-madeira - Lilge, Daniela Silva (2018)
In the wood panels market, cement-wood emerge as a product with interesting characteristics of resistance to biological degradation and great physical and mechanical performance. These panels have wide applicability in construction and has been used on a large scale since the 70s in countries of Europe and especially Asia. Woods commonly used to manufacture these panels come from conifers. However, research on the hardwood performance have shown that these can be a good alternative, since suffering treatment prior to panel manufacturing. The Melia azedarach (cinanmon) species has been evaluated as to his use in the manufacture of reconstituted wood panels and has shown an interesting performance in the manufacture of chipboard panels type. However, its performance in the manufacture of cement-wood panels was not been investigated. Thus, the present work had the objective of evaluating the feasibility of composite panels of cement and particles of cinnamon. For this, the evaluated factors were: methods of preparation of the particles (thermal bath, immersion in aluminum sulfate solution, immersion in sodium hydroxide solution and control); proportions of wood: cement (1:2.5 and 1:3.0); and additives (calcium chloride, magnesium chloride and control). Thus totaling 24 treatments with 5 replicates each. In order to determine the quality of the panels, the physical properties (apparent density, water absorption at 2 and 24 hours of immersion, swelling at 2 and 24 hours of immersion and fire resistance), mechanical strength (modulus of rupture and of elasticity in static flexion, internal bonding and resistance to pulling of screws), besides the resistance of the panels to the attack of white rot fungus (Pycnoporus sanguineus). The panels produced with preparation of the particles by immersion of them in NaOH solution showed less efficiency of the physical and mechanical properties and less resistance to the rotting fungus. The use of additives in the formulation of the panels increased their physical, mechanical and fungus resistance characteristics. The ratio of wood: 1:2,5 cement generated greater mechanical strength of the panels. However, this same proportion caused a worse performance of the panels in terms of their physical properties and resistance to white rot fungus. Therefore, for the manufacture of cement-wood panels of cinnamon, the preparation of the particles with NaOH is not recommended. As for the additives, the use of CaCl2 or MgCl2 is recommended. In the manufacture of these composites, a greater amount of wood in relation to the cement is indicated for panels that need greater mechanical resistance, in other hand for panels whose physical resistance is more relevant, it is indicated the manufacture with a smaller amount of wood in relation to cement.